Olsenella provencensis sp. nov., Olsenella phocaeensis sp. nov., and Olsenella mediterranea sp. nov. isolated from the human colon. (June 2017) - Ricaboni, Davide; Mailhe, Morgane; Vitton, Veronique; Bittar, Fadi; Raoult, Didier; Fournier, Pierre-Edouard
Abstract: We report here the main characteristics of Olsenella provencensis sp. nov., strain Marseille-P2912 T (=CSUR P2912), Olsenella phocaeensis sp. nov., strain Marseille-P2936 T (=CSUR P 2936) and Olsenella mediterranea sp. nov., strain Marseille-P3256 T (=CSUR P3256) that were isolated from human colon samples.